Single‐Molecule Reconstruction of Oligonucleotide Secondary Structure by Atomic Force Microscopy. Issue 16 (17th April 2014) - Pyne, Alice; Thompson, Ruth; Leung, Carl; Roy, Debdulal; Hoogenboom, Bart W.
<x xml:space="preserve">Abstract</x> Based on soft‐touch atomic force microscopy, a method is described to reconstruct the secondary structure of single extended biomolecules, without the need for crystallization. The method is tested by accurately reproducing the dimensions of the B‐DNA crystal structure. Importantly, intramolecular variations in groove depth of the DNA double helix are resolved, which would be inaccessible for methods that rely on ensemble‐averaging. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>